2012
DOI: 10.22358/jafs/66133/2012
|View full text |Cite
|
Sign up to set email alerts
|

The growth performance and meat quality of goats fed diets based on maize or wheat grain

Abstract: A total of 24 four-month-old Liuyang Black wether goats (10±0.2 kg) were allotted to two diets based on wheat and maize to investigate effects of starch sources on the growth performance and meat quality. The experimental period lasted for 100 days, including 10 days for adaptation. Five representative goats from each group were selected for slaughter on the last experimental day. The final body weight and body weight gain of goats in wheat group were lower than those of goats in maize group (P<0.05), however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(43 reference statements)
0
6
1
Order By: Relevance
“…The same study found that certain larvae treated with the insecticide lost their typical C-shape and were either dorsally or dorsolateral elongated and the number of larvae that failed to spin cocoons was greater in the treated larvae groups. On contrary, our results disagree with Zhu et al (2014) who observed that larvae seem to be more tolerant to thiametoxam rather than adults, and Yang et al (2012) who observed that larvae were more tolerant to the imidacloprid when compared with adult of A. mellifera. However, even with the discrepancy in the sensitivity of the honeybee during its development, these authors highlight that the toxic effect of this insecticide at low doses may be harmful and affect the larvae.…”
Section: Data In Tablescontrasting
confidence: 99%
See 1 more Smart Citation
“…The same study found that certain larvae treated with the insecticide lost their typical C-shape and were either dorsally or dorsolateral elongated and the number of larvae that failed to spin cocoons was greater in the treated larvae groups. On contrary, our results disagree with Zhu et al (2014) who observed that larvae seem to be more tolerant to thiametoxam rather than adults, and Yang et al (2012) who observed that larvae were more tolerant to the imidacloprid when compared with adult of A. mellifera. However, even with the discrepancy in the sensitivity of the honeybee during its development, these authors highlight that the toxic effect of this insecticide at low doses may be harmful and affect the larvae.…”
Section: Data In Tablescontrasting
confidence: 99%
“…Honey bee larva can consume 160 ml of brood food before its pupation (Aupinel et al, 2005), it is quite possible that honey bee larvae were affected by the residue of imidacloprid. Yang et al (2012) tested the doses of 0.0004, 0.004, 0.04 and 0.4 nglarva -1 , which corresponds to expose the larvae to an imidacloprid concentration of approximately 0.0025, 0.025, 0.25 and 2.5 mg/L, respectively, which represents the level that is very likely present in an agro-environment. This is strong evidence.…”
Section: Data In Tablesmentioning
confidence: 99%
“…The exploitation of the genetic diversity of various collections of germplasm has been enhanced by the application of molecular markers [ 24 , 27 , 28 ]. Although modern molecular markers such as Single Sequence Repeat (SSR) and Single Nucleotide Polymorphism (SNP) have been developed, the large genome of the genus Vicia (13Gb) is a barrier to the detailed study of genetic diversity at genome level [ 24 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The exploitation of the genetic diversity of various collections of germplasm has been enhanced by the application of molecular markers [ 24 , 27 , 28 ]. Although modern molecular markers such as Single Sequence Repeat (SSR) and Single Nucleotide Polymorphism (SNP) have been developed, the large genome of the genus Vicia (13Gb) is a barrier to the detailed study of genetic diversity at genome level [ 24 , 27 , 28 ]. Yang et al [ 28 ], used 94 Expression Sequence Tag-Single Sequence Repeats (EST-SSR) to classify 32 V. faba genotypes based on their genetic distances and revealed clusters according to their geographical origin [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation